2008
DOI: 10.1002/j.0022-0337.2008.72.10.tb04598.x
|View full text |Cite
|
Sign up to set email alerts
|

Economic Outcomes of a Dental Electronic Patient Record

Abstract: The implementation of an electronic patient record (EPR) in many sectors of health care has been suggested to have positive relationships with both quality of care and improved pedagogy, although evaluation of actual results has been somewhat disillusioning. Evidence-based dentistry clearly suggests the need for tools and systems to improve care, and an EPR is a critical tool that has been widely proposed in recent years. In dental schools, EPR systems are increasingly being adopted, despite obstacles such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…There are barriers that challenges EHR implementation, as the lack of comfort with technologies and the lack of prepared professionals to provide training and support to users; system configuration and maintenance; reporting writing and costs [28,37]. Some cost analysis studies can be found in literature, but only a few addresses the full spectrum of diverse implementation costs, efficiency and costs of health care [77].…”
Section: Resultsmentioning
confidence: 99%
“…There are barriers that challenges EHR implementation, as the lack of comfort with technologies and the lack of prepared professionals to provide training and support to users; system configuration and maintenance; reporting writing and costs [28,37]. Some cost analysis studies can be found in literature, but only a few addresses the full spectrum of diverse implementation costs, efficiency and costs of health care [77].…”
Section: Resultsmentioning
confidence: 99%
“…A review of the literature reveals a dearth of research into the costs of Health IT in medicine, “represent[ing] a major obstacle for decision makers who need reliable information to guide their decisions about EHR implementation.” 8 Information on costs for dental school Health IT is even more scant, 9 a fact that recently resulted in a call for submissions by the editor of this journal 10 . While some cost analysis studies can be found in the medical literature, only a couple address the full spectrum of diverse implementation costs, efficiency, and costs of health care 11 , 12 …”
Section: Build Versus Buy: Complexities Of Health Itmentioning
confidence: 99%
“…The implementation of an EPR requires a large capital expenditure and human resource effort that includes infrastructure, software, hardware, system configuration, documentation, user training and support, report writing, and maintenance of the new system 9 . Other secondary costs include retraining and reassignment of existing staff, ongoing hardware and software costs, compliance, and addition of support staff.…”
mentioning
confidence: 99%